Study on improvement of manpower performance & safety in construction firms - Ananth Purushothaman (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2018)
The construction an industry everywhere faces problems and challenges in the developing countries, this is study aim to improve the manpower of performance and safety of the construction firms. In this project work analyses the safety and manpower performance in the construction firms in additionally the lot of literatures review and build the questionnaires to conduct the survey in the field of constructor. When it is use collect data among the 25 workers to know the risk factors and statistical analysis to give some suggestion still had been reducing the fatigue of workers and increasing facilitate for the work hence develop as well as improve the performance of manpower and performing every construction work in a safe manner.